Penyelesaian Pembiayaan Murabahah yang Bermasalah (KSPPS BMT Mitra Umat Pekalongan Cabang Krapyak) - Nabila, Nurma; Jalaludin, Akhmad; Pratami, Bunga Desyana (el hisbah Journal of Islamic Economic Law, 2022)
Non-performing financing is not expected by financial institutions that provide financing products because it can cause losses to financial institutions. The purpose of this study is to analyze the supporting and inhibiting factors in efforts to resolve problematic murabahah financing at KSPPS BMT Mitra Umat Pekalongan Krapyak Branch in 2021 and analyze the suitability of efforts to resolve problematic murabahah financing at KSPPS BMT Mitra Umat Pekalongan Krapyak Branch in 2021 with the DSN-MUI Fatwa and KHES. This type of research is sociological law with data collection techniques through interviews and documentation. The results of the study show that the supporting factors in efforts to resolve problematic murabahah financing are supervision and communication with customers; customer awareness and good faith; cooperative customers to the agreement; as well as the existence of a team of lawyers who provide a deterrent effect. The inhibiting factor is the character of the customer; customer dishonesty; unstable economic condition; and customers are reluctant to sell collateral. There is a discrepancy with the provisions of the DSN-MUI fatwa and KHES, namely the point of debt relief at the guarantee execution stage, the point of converting a contract. KSPPS BMT Mitra Umat Pekalongan Krapyak Branch does not apply sanctions to customers who delay payments, but charges compensation for transportation costs when billing the customer's home.